Intravaginal misoprostol in the treatment of missed abortion. - Gutierrez, Raymundo (2015)
OBJECTIVE: To evaluate the efficacy of intravaginal mysoprostol to induce abortion in patients with intrauterine fetal death. DESIGN: Prospective, transversal study. MATERIAL AND METHODS: 34 patients (28 with missed abortion and 6 with anembrioned pregnancy) to whom mysoprostol was administered at the dosis of 100 ug, every 4 hours for 4 doses. RESULTS: Success was obtained in 95%, as 28 patients (82.4%) expulsed products of conception and 4 patients (11.7%) had cervical modifications that permited emergency ditalation and curettage. In 75% result was obtained with the second dosis of the product, without associated complications. There were 2 failures. We did not find differences in gestational age, parity, and number of applications required. CONCLUSION: Mysoprostol is an efficacious drug with low cost.